Education in West Kalimantan through the Program of Sekolah Penggerak: Insights into Numeracy Strengthening Practices - Suriyana; Nurdiana, Riyanti; Nur Asmah, Siti (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
Numeracy has become one of the core competencies emphasized in the implementation of the Merdeka Curriculum in Indonesia. However, its practical implementation at the school level continues to encounter various challenges. Empirical studies that examine how numeracy strengthening is enacted in authentic classroom contexts, particularly at the junior secondary school level, remain relatively limited. Therefore, this study aims to analyze the implementation of numeracy strengthening at SMPN 10 Pontianak and SMPN 3 Sungai Kakap in supporting the objectives of the Merdeka Curriculum. This study employed a descriptive qualitative research design. Data were collected through classroom observations and semi-structured interviews with teachers and students to explore instructional practices, learning environments, and assessment strategies related to numeracy development. The findings indicate that teachers in both schools have made considerable efforts to strengthen numeracy by creating supportive learning environments, integrating numeracy-oriented activities into lesson planning, applying appropriate instructional approaches, and implementing project-based assessment practices. Nevertheless, several challenges remain evident. These include students’ difficulties in understanding more advanced numeracy concepts and the relatively limited level of interactivity in the existing assessment practices. In conclusion, while numeracy strengthening has been implemented at a generally satisfactory level, further improvements are still required. Schools are encouraged to enhance student mentoring, strengthen collaboration among teachers, and adopt more flexible and interactive assessment methods to ensure more effective numeracy development in alignment with the goals of the Merdeka Curriculum.